2014
DOI: 10.1111/jcmm.12443
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic basal ganglia calcification‐associated PDGFRB mutations impair the receptor signalling

Abstract: Platelet-derived growth factors (PDGF) bind to two related receptor tyrosine kinases, which are encoded by the PDGFRA and PDGFRB genes. Recently, heterozygous PDGFRB mutations have been described in patients diagnosed with idiopathic basal ganglia calcification (IBGC or Fahr disease), a rare inherited neurological disorder. The goal of the present study was to determine whether these mutations had a positive or negative impact on the PDGFRB activity. We first showed that the E1071V mutant behaved like wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 42 publications
(69 reference statements)
3
52
0
2
Order By: Relevance
“…We surveyed a number of known mediators of this pathway, including STAT3, PLCg1, SRC, and ERK, that have been previously found to be activated by the PDGFRB pathway. 10 Of these putative effectors, we saw evidence that both STAT3 and PLCg1 were phosphorylated by p.Val665Ala PDGFRB in the absence of PDGF-BB (time point 0 min in Figures 6B and 6C), whereas neither SRC nor ERK showed evidence of increased signal transduction as compared that in the wild-type protein (Figures 6D and 6E).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We surveyed a number of known mediators of this pathway, including STAT3, PLCg1, SRC, and ERK, that have been previously found to be activated by the PDGFRB pathway. 10 Of these putative effectors, we saw evidence that both STAT3 and PLCg1 were phosphorylated by p.Val665Ala PDGFRB in the absence of PDGF-BB (time point 0 min in Figures 6B and 6C), whereas neither SRC nor ERK showed evidence of increased signal transduction as compared that in the wild-type protein (Figures 6D and 6E).…”
mentioning
confidence: 86%
“…7,10 It is reasonable to conclude that IBGC4 is caused by a reduced signal-transduction capacity of this protein.…”
mentioning
confidence: 97%
“…It has been demonstrated that the missense mutation p.Leu658Pro reduces the kinase activity, while p.Arg987Trp mutation causes a rapid degradation of the receptor and impairs the activation of STAT3, a transcription activator, blocking the downstream signalling. On the other hand, the mutation p.Glu1071Val does not affect the phosphorylation and the signalling and probably it might be a polymorphism [28]. It has been hypothesized that the loss of function of PDGFRb could lead to the impairment of the blood brain barrier (BBB) integrity, [2] c.1802C[T p.Ser601Leu Exon 11 [2,22] c.1828_1831delTCC p.Ser610Alafs*17 Exon 11 [22] c.1909A[C p.Ser637Arg Exon 11 [37] g.42275321_42329908del Whole gene [24] Neurol Sci causing vascular and perivascular calcium accumulation [3].…”
Section: Pdgfrbmentioning
confidence: 96%
“…Bunlar; SLC20A2, PDGFRB, PDGFB ve XPR1'dir. [5] Bununla birlikte, hastaların ço¤unda, genetik bir geçi saptanmamıtır. ‹ki taraflı bazal gangliyon kalsifikasyonlarının görülme sıklıkları düük olmakla birlikte, bu durum özellikle hipoparatiroidizmde ve kalsiyum -fosfor metabolizma bozukluklarında gözlenmektedir.…”
Section: öZunclassified